Knowledge about ethical issues in the use of human teeth among undergraduate dentistry students and dentists (Research, Society and Development, 2021)
The aim of this study was to assess the knowledge of dentists (CD) about ethical issues involving human teeth. This is a cross-sectional study, carried out with a CD in the city of Cajazeiras, Paraíba, Brazil. For data collection, a questionnaire was applied via Google Forms. In it, questions about ethics, dental extraction and human tooth bank (BDH) were presented. Dentists registered with the Regional Council of Dentistry (CRO) who work in Alto Sertão Paraibano were included and the search for professionals was carried out directly at the CRO, by email and telephone. Those who did not completely fill out the form were excluded. This study was approved by the Research Ethics Committee under opinion No. 5056616. Data analysis was performed using descriptive analysis of the results. Eighteen CDs who work in the upper sertão of Paraíba participated, aged between 22 and 41 years old. Among these, most were female, had graduated from the private school system and considered the tooth as an organ. More than half of CDs said they would donate teeth extracted in their offices to the tooth bank. Still, almost all of them never donated teeth extracted in their offices to the BDH. Most dentists in this study are unaware of the existence of BDH in the state, the legal prerogatives involving the subject and the necessary procedures for donating teeth to banks.